Immunohistochemical protein expression profiling of growth- and apoptotic-related factors in relation to umbilical cord length. Issue 5 (May 2015) - Olaya-C, Mercedes; Fritsch, Michael; Bernal, Jaime E.
Abstract Introduction Umbilical cord (UC) alterations are related to fetal and neonatal deaths and late neurological complications. Abnormal UC length has been recognized as the most significant abnormality linked to unfavorable outcomes. Despite its importance, causal factors resulting in abnormally long or short UCs have yet to be established. The factors that govern UC length are largely unknown. Furthermore, there is a paucity of studies that assess molecular processes involved in the establishment of UC length. We hypothesize that UC length abnormalities in UC length are associated with altered protein expression patterns of known cell growth and/or apoptosis regulators. In this study we analyze diverse protein expression patterns in different UC cell types found in UCs of normal and abnormal length. Methods An analytical observational study was carried out on fetal autopsies; diagnosed abnormal length UCs were compared to normal controls by gestational age. Immunohistochemical analysis of expression levels of growth and pro- and anti-apoptotic factors was performed. Results We performed immunohistochemistry antibody tests against FAS, BAX, Ki67, cMyc, FGF2, TGFBR3, VEGF, Bcl2, p57 and IGF2 and analyzed UC cell expression patterns. We found significant differences in specific long and/or short cord cell types in comparison to those in normal cords. Discussion Factors that determine UC length are still largely unknown; however, this study demonstrates significant specific cell type differences in protein expression patterns of several genes related to cell proliferation. This preliminary study provides strong supporting data to continue the search for molecular factors that determine UC length.